The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.cellbi.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and sex on the spontaneous DNA damage detected by Micronucleus test and Comet assay in mice peripheral blood cells

Abstract: We have investigated the normal variations in basal DNA damage detected by Comet assay in leukocytes and micronucleated erythrocytes (MNE) using the Micronucleus test (MN) in peripheral blood cells from 45 female and male mice from different age groups (newborns, 3.5, 12, and 104 weeks) to clarify age and sex-related changes. Comparison of basal DNA damage detected by Comet assay showed significantly increased values in 104 weeks old mice in relation to the other ages (P < or = 0.01), and newborn mice showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 51 publications
3
26
2
2
Order By: Relevance
“…They can also be caused by chemical reactions related to physiological processes. 9 In addition to age, studies have shown that differences in the occurrence of genetic damage can also be related to gender. [10][11][12] Trzeciak et al 11 reported that the removal of active carcinogens through tobacco is lower in women, thereby indicating biochemical differences between the genders.…”
Section: Introductionmentioning
confidence: 99%
“…They can also be caused by chemical reactions related to physiological processes. 9 In addition to age, studies have shown that differences in the occurrence of genetic damage can also be related to gender. [10][11][12] Trzeciak et al 11 reported that the removal of active carcinogens through tobacco is lower in women, thereby indicating biochemical differences between the genders.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with Joseph et al [19], who have stated an association between micronuclei and metastasis but no correlation with age or sex. However, Heuser et al [20] showed a positive relationship between spontaneous DNA damage in comet and micronuclei assays and age in mice.…”
Section: Discussionmentioning
confidence: 97%
“…The Comet assay is used to detect primary DNA lesions (i.e., single or double strand breaks), while the MN assay is used to detect structural and numerical chromosomal damage. Additionally, the comet assay determines strand breaks and labile sites that are subsequently removed by repair enzymes (Heuser et al, 2008). In this study, both of the detecting techniques were successfully applied in detecting DNA damage in the two different drinking water treatment processes.…”
Section: Discussionmentioning
confidence: 99%